La morte e i suoi riti in Italia tra Medioevo e prima Età moderna - Gian Maria Varanini (Centro di Studi sulla Civiltà del Tardo Medioevo San Miniato, 2007)
Consciously repressed by the current dominating culture, in Italy and Europe in the late mediaeval and early modern age death was addressed with greater confidence and awareness, and sometimes even with serenity. The modes of dying and of conceiving death - and the varied and rich religious and civil rituals that accompanied it - reflected the values and the choices of rich and poor, of kings and peasants, merchants and soldiers, nobles and churchmen, men and women. Several decades after the major studies that opened the road to these strands of research in Italy too (Ariès, Tenenti), this book offers a series of penetrating and suggestive explorations of a fascinating and complex theme which no reader can consider extraneous.